Manisa İli'nde özkıyım girişimlerine ilişkin özellikler: Beş yıllık verinin değerlendirilmesi/Retrospective evaluation of attempted suicides based on a register in the province of Manisa: Age and gender based variations of methods and reasons - Hatice Şimşek; Guljan Donmez; Tolga Binbay; Erdem Erkoyun; Reyhan Uçku (Turkish Society of Public Health Specialists, 2014)
Özet Amaç: Manisa'da 2007-2011 yılları arasındaki özkıyım girişiminde bulunan olguların özelliklerinin cinsiyete göre incelenmesidir. Yöntem: Tanımlayıcı tipteki araştırma, Manisa Halk Sağlığı Müdürlüğü'nün intihar girişimleri kayıt formlarının incelemesiyle yapılmıştır.  Bulgular: Toplam 6827 olgunun 5311'i (%77.8) kadındır. Özkıyım girişiminde bulunan olguların %57.3'ü 15-24 yaş grubunda, %51.6'sı bekar, %62.2'si ilköğretim mezunudur. Olguların %95.8'inin özkıyım girişimi yöntemi zehirleyici maddedir. En yaygın özkıyım nedeni genel toplamda ve kadınlarda aile geçimsizliği-evlilik-çocuklarken, erkeklerde ruhsal hastalıktır. Özkıyım nedeni en sık, 15 yaş altında ve 15-24 yaş grubunda ebeveyn çatışmaları, 25-64 yaş grubunda aile geçimsizliği-evlilik-çocuklar, 65 yaş ve üzerinde ruhsal ve bedensel hastalıktır. Sonuç: Özkıyım girişiminde bulunan olguların çoğunluğu kadın, ergen/genç yaş grubu, ilköğretim mezunu olanlar, çalışmayanlardır. Başlıca özkıyım girişimi yöntemi ilaç ve zehirleyici madde kullanımıdır. Nedenler de yaş grubu ve cinsiyete göre değişmektedir. Anahtar Kelimeler: Özkıyım,  özkıyım girişimi, epidemiyoloji, risk etmeni Abstract Objective: The study determined, by gender and age group, the characteristics of individuals who had attempted suicide in Manisa between the years 2007-2011. Method: This was a descriptive study conducted by retrospective research of "suicide attempt entry forms". Results:A total of 6827 suicides were evaluated. 5311 (77.8%) were women, 57.3% were aged 15-24 years, 51.6% were single, 62.2% had graduated from primary schools. In 95.8% of the suicides the method of suicide was self-poisoning with drugs. The most common reasons for the suicide attempts in total and among women were family problems, marriage and children; mental illness among men. The most frequent reasons for the suicide attempts among those who were 15-24 years of age were conflicts with parents; among the age group of 25-64 the reasons were family problems, marriage or children, and among those who were 65 years and over the reasons were mental or physical illnesses. Conclusion: The main determinants of suicide attempts were female gender, adolescents and/or young adults, primary school as an educational level, unemployed individuals. The most frequent suicide method was self-poisoning. Reasons of attempts displayed variation based on age group and gender. Key words:  suicide, suicide attempt, epidemiology, risk factor